Children's influence on family dynamics : the neglected side of family relationships - Crouter, Ann C.; Booth, Alan, 1935-2015 (Lawrence Erlbaum Associates, 2003)
This volume addresses how children's personal qualities make their mark on families in ways that may in turn influence children's subsequent development.